Dietary Strawberries Lower Branched Chain Amino Acids in Adults With the Metabolic Syndrome in Targeted Serum Metabolomics Analyses. (14th June 2022) - Basu, Arpita; Izuora, Kenneth; Scofield, Hal
Abstract: Objectives: Dietary berries have been shown to lower cardio-metabolic risks in clinical trials. We examined the dose-response effects of two dietary achievable doses of strawberries on serum metabolomics related to energy metabolism in adults with metabolic syndrome. Methods: In this 14-week randomized controlled crossover study adults with metabolic syndrome were assigned to one of the three arms for 4 weeks separated by a one-week washout period: control powder, one serving strawberries (13 g powder/day), and 2.5 servings strawberries (32 g powder/day). The freeze-dried powders were blended in water and participants consumed half the daily dose in the morning and half in the evening. Participants were instructed to follow their usual diet and lifestyle while refraining from consuming other berries and related products throughout the study. Metabolic profiling was performed using a high-throughput serum nuclear magnetic resonance (NMR) metabolomics platform (West Coast Metabolomics Center, UC Davis, USA). Results: Thirty-three participants completed all three phases of the trial (baseline profiles: weight: 90.8 ± 22.4 kg, BMI: 33.1 ± 4.2 kg/m 2, waist circumference: 109 ± 12.5 cm, HbA1c :5.8 ± 0.2%). Outcome measures were analyzed using a multivariate analysis of variance with statistical significance set at p < 0.05. Among the targeted primary metabolites, strawberry supplementation at a dose of 2.5 servings per day for 4 weeks significantly decreased the circulating concentrations of branched chain amino acids (valine and leucine) as targeted primary metabolites in the study (P < 0.05). No effects were noted on isoleucine, alanine, and other metabolites of the citric acid cycle. Conclusions: These branched chain amino acids are increased in individuals with obesity and are associated with insulin resistance or type 2 diabetes. These data suggest that consuming strawberries at two and half servings for four weeks significantly improves metabolomic profiles related to insulin resistance in adults with the metabolic syndrome. Funding Sources: California Strawberry Commission and NIH COBRE.